Faktor Risiko yang Berhubungan dengan Kejadian Haemoragic Post Partum di Rumah Bersalin Wijaya Kusuma Tahun 2014 - Fijriah, Putri Noorrizky; Fauziah, Munaya (Universitas Ahmad Dahlan, 2016)
Background: Haemoragic postpartum is one of the important issues related to maternal health because it can cause death. Method: This study aimed to analyze the risk factors which related to the events in the maternity hospital haemoragic postpartum Wijaya Kusuma Serpong in 2014. The sample of this study was 313 maternal. This research was descriptive analytic with cross sectional approach. Results: The results of this study showed that the prevalence of postpartum haemoragic in Wijaya Kusuma Serpong was 13.1%. There was a significant correlation between the incidence of haemoragic postpartum with age (p=0.000), parity (p=0.047), atonic (p=0.000), retained placenta (p=0.000). While no significant correlation between the incidence of haemoragic postpartum with education (p=0.087), and employment (p=0.588). Conclusion: Is needed improving knowledge of pregnant women to be aware of the possibility of haemoragic postpartum.